Qualifi ers applied to wine in Iliad and Odyssey (Circe de clásicos y modernos, 2018)
The article attends to detect the prevailing qualities attributed to oinos and methy in the Homeric poems; to elaborate a record, to classify into a hierarchy depending on specific parameters such as color, gradation, bouquet (aroma, flavor, strength, among other sensations), to weigh the implicit consideration either positive or negative, to observe the common location in the hexameter, compare with further nouns which also accompany the above mentioned adjectives (or participles with adjective function), to examine Latin equivalents and, without avoiding the qualitative consistency of the own beauty of art, offer some reasons for which the studied corpus is applied in both texts.
Keywords: Illiad; Odyssey; wine; epithets